2016
DOI: 10.1101/039818
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing the relationship between height growth and molecular genetic variation in Douglas-fir (Pseudotsuga menziesii) provenances

Abstract: Douglas-fir (Pseudotsuga menziesii) is a conifer tree native to western North America. In central Europe, it shows superior growth performance and is considered a suitable substitute for tree species impaired in vitality due to climate change. Maintenance and improvement of growth performance in a changing environment is a main challenge for forest tree breeders. In this context, genetic variation as a factor underlying phenotypic variation, but also as the basis for future adaptation, is of particular interes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 68 publications
1
17
0
Order By: Relevance
“…This loss in previously fixed CO 2 can be substantial and for beech seedlings it was shown that it can even result in reduced growth29. Previously it was shown that interior provenances reveal reduced growth compared to coastal provenances6, an observations that is also confirmed for the provenances studied here and at our field sites58, Based on our observations, increases in the allocation of previously fixed CO 2 to the biosynthesis of monoterpenes for storage and emission in the provenance SAL might therefore affect its growth performance compared to coastal provenances.…”
Section: Discussionsupporting
confidence: 87%
“…This loss in previously fixed CO 2 can be substantial and for beech seedlings it was shown that it can even result in reduced growth29. Previously it was shown that interior provenances reveal reduced growth compared to coastal provenances6, an observations that is also confirmed for the provenances studied here and at our field sites58, Based on our observations, increases in the allocation of previously fixed CO 2 to the biosynthesis of monoterpenes for storage and emission in the provenance SAL might therefore affect its growth performance compared to coastal provenances.…”
Section: Discussionsupporting
confidence: 87%
“…The origins differ in elevation (AR: 650 m, LA: 210 m), mean annual temperature (AR: 7.8 °C, LA: 10 °C) and most importantly in mean annual precipitation (AR: 500 mm, LA: 1475 mm). Recent studies using SNP [77] and microsatellite markers [78] revealed a clear genetic differentiation of these two provenances. For this study we used 50-year-old Dougls-fir trees from two common garden experiments near Schluchsee (S; 47°84′ N, 8°11′ E) and Wiesloch (W; 49°30′ N, 5°53′ E) in south-western Germany.…”
Section: Methodsmentioning
confidence: 99%
“…The two sites differ in annual precipitation (S: 1345 mm, W: 660 mm) as well as in elevation (S: 1050 m, W: 105 m above sea level) and annual mean temperature (S: 6.1 °C, W: 9.9 °C). A detailed description of the provenances and the two field sites can be found in [78, 80]. At each field site needle samples were taken repeatedly from 8 trees per provenance and on four different dates during the 2010 growing season (in Schluchsee on May 27, June 30, July 28, September 15; in Wiesloch on May 12, June 16, July 14, September 8; these eight sampling dates reflect the levels of the factor DATE that was used for modeling of gene expression, see below).…”
Section: Methodsmentioning
confidence: 99%
“…Especially the nSSRs developed by Slavov (2004) have been applied in several studies (e.g. Krutovsky et al 2009, Sk Lai et al 2010, Fussi et al 2013, Neophytou et al 2016, van Loo et al 2015, Korecký and El-Kassaby 2016, Hintsteiner et al 2018).…”
Section: Important Resultsmentioning
confidence: 99%
“…These markers were used in different studies on genetic variability of Douglas-fir populations (e.g. Krutovsky et al 2009, Fussi et al 2013 3,4,5,6,7,8,9,10,11,12 PmOSU_3B2 1-Amarasinghe and Carlson 2002, 2-Slavov et al 2004, 3-Slavov et al 2005, 4-Krutovsky et al 2009, 5-Sk Lai et al 2010, 6-Konnert and Fussi 2012, 7-Fussi et al 2013, 8-Korecký and El-Kassaby 2016, 9-van Loo et al 2015, 10-Neophytou et al 2016, 11-Eckhart et al 2017, 12-Hintsteiner et al 2018 Material for DNA-extraction DNA has been extracted from needles (Neophytou et al 2016, Fussi et al 2013, Slavov et al 2004, van Loo et al 2015, Eckhart et al 2017, Hintsteiner et al 2018), buds (Slavov et al 2005, Sk Lai et al 2010…”
Section: B) Nssrs (Putatively Neutral Microsatellites) Loci and Primementioning
confidence: 99%